Evaluation of the physiological parameters, quality of sedation and reversal with the use of atipamezole in mules (Equus) sedated with dexmedetomidine - M.R.T. Santos; M.P. Beiriz; A.G. Carreira; C.C. Mendonça; E.E.G. Souza; A.J.F. Santos; A.P. Gering; K.S. Almeida; M.A.G. Silva (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The objective of this study was to evaluate the sedative, cardiorespiratory, and intestinal motility effects of dexmedetomidine administered intravenously in mules, before and after the use of the reversal agent. All animals were sedated with the recommended dose, with a significant decrease in HR until T30, returning to close to baseline values at T40. MINT reduced significantly between T10 and T50. Significant hyperglycemia was observed at T10. A significant reduction in head height was detected, with the highest values being observed at T20. In relation to tactile, auditory, and coordination stimuli, a significant reduction was noted, for the first two until T30 and for the latter until T10. After using the reversal agent, MINT returned to normal. It is concluded that the use of dexmedetomidine at a dose of 5mcg/kg in mules is safe and that it promotes a sedative effect for a period of 30 minutes. Furthermore, attention should be paid to the undesirable effect on intestinal motility, as this increases the predisposition to colic syndrome; the reversal agent atipamezole is effective for reversing intestinal motility.